Association between type of school and student achievement in urban areas (Revista Peruana de Investigación Educativa, 2015)
Over the past years, access to basic education has increased significantly. However, learning levels remain low and the progress that has been achieved is not enough to guarantee a good education. Given this context, exploring the factors associated with student achievement becomes an important issue. Using a longitudinal data base, this study seeks to estimate the effect of the type of school - public or private - in the urban area, on children´s achievemnt aged 7-8 years in math and vocabulary (PPVT). Results show that attending a private school has a positive and significant effect in math but not in vocabulary. This may be because learning math depends more on the curriculum implemented in schools while children’s vocabulary may also be influenced by the family. Finally, the difference in the PPVT score between children attending public and private schools is mainly explained by children´s previous achievements; while in mathematics, the gap is mainly explained by variables associated to the child and his family.
Keywords: type of school; private school; urban education; student achievement; Peru